VirtualECare: intelligent assisted living - Costa, Ricardo André Fernandes (2009)
Innovative healthcare projects are arising in today’s society, normally presenting as major advantage the reduction of care provider’s costs. Being these advantage a legitimate one, we are trying to take it a step forward through the use of proactiveness, decision making techniques, idea generation, argumentation and quality, not only of the in transit information, but also of the provided service as well. With these objectives in mind, the VirtualECare project was born. In this paper we are going to briefly present the project and make a position of the actual developments in this first year of work.